How Does Environmental Regulation and Digital Finance Affect Green Technological Innovation: Evidence From China - Ma, Ruowei; Li, Feifei; Du, Mingyue (Frontiers in Environmental Science, 2022)
With the deteriorating ecological environment, green technological innovation (GTI) has become an effective way to strengthen environmental protection and promote economic development. Based on the 2011 to 2019 panel data of 30 provinces in China, this study constructs a spatial Durbin model to examine the spatial spillover effect of environmental regulation and digital finance on green technological innovation. Meanwhile, a moderating effect model and threshold effect model are employed to explore the function of digital finance in terms of the impact of environmental regulation on green technological innovation. The empirical results show that: (1) environmental regulation has significantly promoted local green technological innovation, green invention patents (GIP) and green utility model patents (GUP), while having had negative spatial spillover effects on those three things in neighboring regions. Digital finance promotes green technology innovation and green invention patents in both local and neighboring areas, but digital finance’s direct and spatial spillover effects on green utility model patents are not significant. (2) A regional analysis shows that different intensities of environmental regulation and different digital finance levels in different regions lead to the heterogeneity of green technological innovation's response to them. (3) Digital finance is an important moderating variable of environmental regulation’s effect on green technology innovation. Digital finance produces a positive moderating effect on environmental regulation affecting green technology innovation and green invention patents in local and neighboring regions. However, digital finance’s moderating effect in terms of the influence of environmental regulation on green utility model patents is not significant. (4) Digital finance is the threshold variable of environmental regulation’s effect on green technology innovation. Specifically, if the degree of digital finance reaches a certain threshold, the promotion effect of environmental regulation on green technology innovation will be stronger.